Curiosity in the Austrian Enlightenment - Robertson, R (W. S. Maney & Son Ltd., 2009)
Catholic culture is popularly supposed not to be conducive to curiosity. Yet the Austrian Enlightenment, which reached its peak in the 1780s but had intellectual and institutional roots earlier in the eighteenth century, encouraged curiosity - sometimes unofficial - in many areas. The three here examined are: the study of the Bible and Church history; natural science; and ethnography, or the description of foreign peoples, a genre which developed from travel literature and became fully established at the end of the century.